From Poison to Promotor: Spatially Isolated Metal Sites in Supported Rhodium Sulfides as Hydroformylation Catalysts - Arjun Neyyathala; Edvin Fako; Sandip De; Daria Gashnikova; Florian Maurer; Jan‐Dierk Grunwaldt; Stephan A. Schunk; Schirin Hanf (Small Structures)
The hydroformylation of alkenes is a cornerstone transformation for the chemical industry, central for both functionalizing and extending the carbon backbone of an alkene. In this study, silica‐supported crystalline rhodium sulfide nanoparticles are explored as heterogeneous catalysts in hydroformylation reactions, and it is found that RhxSy systems (x = 17, y = 15 or x = 2, y = 3 with 1 wt% Rh on SiO2) greatly outperform metallic Rh nanoparticles. These systems prove to be exceptionally competitive when benchmarked against other cutting‐edge catalysts in terms of activity, with Rh17S15/SiO2 being the superior catalyst candidate. By employing local environment descriptors, unsupervised machine learning and density functional theory, the structure‐performance relationships are examined. The results highlight that the presence of S in close proximity to the catalytic site unlocks the tunability of the surface catalytic properties. This allows for the substrate affinity to be modulated, in particular for Rh17S15, with adsorption energies rivalling those of pristine Rh and improved spatial resolution.